Pengaruh Promosi Online, Inovasi Produk, dan Citra Merek terhadap Daya Saing Produk Peralatan Bucket Bunga di Batam - Amanda Bella Shakira; Yandra Rivaldo; Rosita Septiani (Jurnal Manajemen Riset Inovasi, 2026)
The purpose of this study is to examine how online promotion, product innovation, and brand image affect product competitiveness in Batam City's flower bucket equipment industry (CV Acmeteam). This study employs a quantitative methodology, gathering information from 100 respondents via questionnaires using Simple Random Sampling with Slovin formula from a population of 135 active customers. Data were analyzed through validity tests, reliability tests (Cronbach's Alpha = 0.750), classical assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression, partial t-test, simultaneous F-test, and coefficient of determination (R²). Results show that all questionnaire items are valid and reliable. The normality test (Asymp. Sig. = 0.866 > 0.05) indicates normally distributed data, and no multicollinearity (VIF < 10) or heteroscedasticity (Sig. > 0.05) was detected. Regression analysis reveals that online promotion (β = 0.521, Sig. = 0.041), product innovation (β = 0.668, Sig. = 0.033), and brand image (β = 0.458, Sig. = 0.049) each significantly influence product competitiveness. Simultaneously, all three variables are significant (F = 9.876, Sig. = 0.000) and explain 44.9% (R² = 0.449) of product competitiveness variance. Product innovation is the strongest predictor. This study concludes that strong brand image, continuous product innovation, and effective digital marketing are essential pillars for enhancing product competitiveness. Business actors must optimize these three elements to compete effectively in an increasingly open creative industry market.